2020
DOI: 10.1016/j.uclim.2020.100646
|View full text |Cite
|
Sign up to set email alerts
|

Developing a GIS tool for emergency urban cooling in case of heat-waves

Abstract: Many cities are expected to face a strong increase in the frequency and intensity of heatwaves by the end of the 21 st Century due to climate change. In Paris, the frequency of heatwaves could rise from an average of one day per year to 14-26 days per year, with temperatures reaching up to 50°C. Since 2012, pavementwatering is viewed as a potential tool for emergency cooling by the city while scientific work on the technique has found its application to be best suited to densely built urban areas, compared for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…To tackle this aspect, a GIS tool can be used to identify priority areas in terms of population exposure and vulnerability, foreseeing their redesigning into cooler areas. Such tool aims to propose cooling solutions adapted to the sites identified depending on their cooling potential (Hendel et al 2019). On this basis, other simple cooling solutions may be proposed, such as sun-shading or vegetation.…”
Section: Resultsmentioning
confidence: 99%
“…To tackle this aspect, a GIS tool can be used to identify priority areas in terms of population exposure and vulnerability, foreseeing their redesigning into cooler areas. Such tool aims to propose cooling solutions adapted to the sites identified depending on their cooling potential (Hendel et al 2019). On this basis, other simple cooling solutions may be proposed, such as sun-shading or vegetation.…”
Section: Resultsmentioning
confidence: 99%
“…Laaidi et al [32] found that during the 2003 heat wave in France, exposure to high nighttime minimum temperature was significantly correlated with the elderly mortality rate. This will be exacerbated in the future based on studies that predict the increase in heat wave length by up to 25 days per year [33]. Similar results from studies of the 1995 Chicago heat wave showed the harmful impacts of high nighttime temperature [6].…”
Section: Introductionmentioning
confidence: 85%
“…Estimates of green cooling vary spatially and range from 7 • C [34] to 10 • C [35] for parks and 1.5 • C near street trees, with green walls providing limited cooling near the wall surface [36]. Smith and Roebber [37] modeled green roofs in Chicago, IL, and found that green roofs can decrease local temperatures by up to 3 • C. In addition, some cities are using pavement watering as a temporary solution for urban heat reduction emergency plans [33]. This method helps cities with a lack of available green spaces, while it is useful for those with available water resources for watering purposes [33,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…In the paper, we propose to study the thermo-climatic behaviour of different conventional Parisian road materials (asphalt road, asphalt and granite sidewalks and stabilized sand) and alternatives (concrete sidewalk and thermochromic and near-infrared reflective paints) undergoing heat-wave-like conditions inside a climate chamber, including a day phase with artificial insolation and a night phase (Hendel et al 2018). A water sprinkler device also allows the control of the watering rate of the surfaces in order to determine the optimal rate and the maximum cooling effects of this method.…”
Section: Introductionmentioning
confidence: 99%